Ultrasound-Guided Percutaneous Thermal Ablation of Hepatic Focal Nodular Hyperplasia——A Multicenter Retrospective Study - Yu, Xuan; Chang, Jiandong; Zhang, Dezhi; Lu, Qiang; Wu, Songsong; Li, Kai (Frontiers in Bioengineering and Biotechnology, 2022)
Background and Aim: To evaluate the clinical effect of ultrasound (US)-guided percutaneous thermal ablation of hepatic focal nodular hyperplasia (FNH). Methods: A retrospective analysis of the clinical data of patients undergoing US-guided percutaneous thermal ablation of FNH from November 2008 to August 2021 at 5 medical centers in China was conducted. Results: A total of 53 patients were included (26 males and 27 females). The mean age was 35.1±10.8 years. Sixty-five lesions (46 solitary cases and 7 cases with multiple lesions) were included, 70.8% (46/65) of which were located in the right liver lobe. The mean tumor length was 2.9 cm±1.5 cm. All patients successfully completed the ablation treatment. Immediate postoperative imaging showed that the primary technical success rate was 94.3% (50/53). Two patients underwent ablation 3 months and 6 months after the primary ablation, and the secondary technical success rate was 100% (2/2). The incidence of complications was 3.8% (2/53). Imaging follow-up was conducted regularly after ablation, and no residual lesion enlargement or tumor recurrence was observed during the follow-up period. The technique efficacy rate was 98.1% (52/53). Conclusions: US-guided percutaneous thermal ablation is a safe and effective treatment for FNH of the liver.